FATNESS OF THE CLAM, MERETRIX CASTA (CHEMNITZ) - Durve, V S; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
The quality of the clam Meretrix casta from two different localities at Athankarai estuary and marine fish farm at Mandapam was assessed by three methods. It was found that clams inhabiting Athankarai estuary were of better quality than those from the fish farm. The probable caiise appears to be the better nutritional conditions in the natural habitat of Athankarai estuary along with the free-flowing water and moderate salinity prevailing there.